2020
DOI: 10.1111/cas.14268
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of multiple pancreatic cancers involves multicentric carcinogenesis and intrapancreatic metastasis

Abstract: There are increased opportunities in oncology clinics to identify multiple pancreatic ductal adenocarcinomas (PDAC) that co‐occur simultaneously or arise metachronously in the pancreatic parenchyma, yet their pathogenesis remains elusive. We hypothesized that two potential pathways, multicentric carcinogenesis and intrapancreatic metastasis, might contribute to forming multiple PDAC. Among 241 resected cases, we identified 20 cancer nodules from nine patients with multiple PDAC (six with synchronous PDAC, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
(63 reference statements)
2
16
0
Order By: Relevance
“…In the current case, some small peritoneal disseminations were observed that were discontinuous from the main lesion. Similar pathological findings and dismal prognoses have been observed in cases of intra-pancreatic metastasis or multi-centric carcinogenesis[ 36 , 37 ]. Therefore, if a small cancerous lesion is observed within the pancreatic parenchyma, it needs to be differentiated from needle tract seeding.…”
Section: Discussionsupporting
confidence: 72%
“…In the current case, some small peritoneal disseminations were observed that were discontinuous from the main lesion. Similar pathological findings and dismal prognoses have been observed in cases of intra-pancreatic metastasis or multi-centric carcinogenesis[ 36 , 37 ]. Therefore, if a small cancerous lesion is observed within the pancreatic parenchyma, it needs to be differentiated from needle tract seeding.…”
Section: Discussionsupporting
confidence: 72%
“…In PDAC, the decreased expression of SMAD4 identified by the immunolabeling of resected specimens has been reported to be associated with poor prognosis 14,38‐40 . In NGS, SMAD4 mutations are considered a poor prognostic factor in the analysis of DNA extracts from resected PDAC cells purified from cell lines or xenografts, 21 whereas they were not a prognostic factor in the analysis of DNA extracts from FFPE or fresh‐frozen specimens. To our knowledge, the current study is the first to report SMAD4 mutations as a prognostic factor for PDAC in NGS analysis using DNA extracts from FFPE.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing DNA extracts from fresh‐frozen samples, Hayashi et al 20 revealed that the number of driver gene mutations could be a prognostic factor; however, certain gene mutations associated with prognosis were not detected. Based on NGS analysis using FFPE samples, we previously reported that multiple PDAC involves multicentric carcinogenesis and intrapancreatic metastasis, which could be distinguished by comparing driver gene mutations; the latter has a dismal prognosis 21 . According to the NCCN Guidelines of 2019, somatic mutational profiling of tumor tissue is recommended for PDAC 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors that metastasize to the pancreas include pancreatic cancer and other organ malignancies [15,16]. Tumor metastasis from other organs to the pancreas is rare and occurs in approximately 2% of pancreatic tumors [7].…”
Section: Discussionmentioning
confidence: 99%